Harnessing spiritual coping to foster resilience: insights from post-trauma mental health after the Kahramanmaraş earthquake - Okan, Nesrullah; Sahin, Yahya; Genc, Hulusi; Demirhan, Mehmet (Springernature, 2025)
The objective of this study was to examine the protective effects of spiritual coping on post-traumatic stress, anxiety, and depression, and its contribution to well-being in individuals affected by the Kahramanmara & scedil; earthquake on 6 February 2023. This study was based on the premise that spiritual coping acts as a protective factor against psychological distress. It aimed to identify the mechanisms through which spiritual coping alleviates the negative psychological effects of trauma and enhances mental health. The study sample comprised 382 individuals, the majority of whom (75.9%) were women, aged between 16 and 50, primarily young adults, who had experienced varying levels of impact from the earthquake. Structural equation modelling (SEM) was employed to analyse both the direct and indirect effects of spiritual coping on depression, stress, and anxiety. The findings indicated that spiritual coping was associated with a notable reduction in psychological distress, including stress, anxiety, and depression, and an increase in overall well-being. Furthermore, the model illustrated that spiritual coping contributes to enhanced psychological resilience by fostering adaptive mechanisms in the aftermath of trauma. These findings indicate that the incorporation of spiritual coping strategies into post-trauma interventions may prove an effective means of enhancing individuals' mental health and resilience.
Keywords: Stress-Disorder; Depression; Anxiety; Happiness; Symptoms; Growth; Scales